Pengaruh Remote Audit dan Teknologi Informasi terhadap Kualitas Audit BPK Sulawesi Barat: Studi Empiris pada Badan Pemeriksa Keuangan Republik Indonesia (BPK) Perwakilan Provinsi Sulawesi Barat - Tri Devi (Jurnal Literasi Akuntansi, 2025)
Purpose: This study analyzes the impact of remote audits and information technology on audit quality at the Audit Board of the Republic of Indonesia (BPK RI) Representative Office of West Sulawesi Province. Motivated by national budget efficiency policies, it examines whether digital-based auditing enhances effectiveness, accuracy, and credibility of audit results despite limited resources. Method: This study used a quantitative causal approach with 36 purposively selected auditors from BPK RI West Sulawesi. Data were collected via online questionnaires and analyzed using multiple linear regression in SPSS 30, supported by classical assumption tests to ensure model validity. Finding: The results show that both remote audit and information technology have a positive and significant effect on audit quality, either partially or simultaneously. The coefficient of determination (R²) of 0.670 indicates that 67% of audit quality variations are explained by these two variables. This finding confirms that digital audit practices improve efficiency, timeliness, and the accuracy of financial examination in the public sector. Novelty: This study differs from previous works by providing empirical evidence from the Indonesian public sector, specifically the BPK RI West Sulawesi Office, where digital audit implementation occurs under strict budget efficiency policies. Unlike prior studies focusing mainly on private-sector or theoretical perspectives, this research examines how limited resources and institutional digital transformation jointly shape audit quality in a developing-country context.